2001
DOI: 10.1074/jbc.m007650200
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Urokinase Expression and Invasiveness by Urinary Trypsin Inhibitor Is Mediated through Inhibition of Protein Kinase C- and MEK/ERK/c-Jun-dependent Signaling Pathways

Abstract: Urinary trypsin inhibitor (UTI), a Kunitz-type protease inhibitor, interacts with cells as a negative modulator of the invasive cells. Human ovarian cancer cell line, HRA, was treated with phorbol ester (PMA) to evaluate the effect on expression of urokinase-type plasminogen activator (uPA), since the action of uPA has been implicated in matrix degradation and cell motility. Preincubation of the cells with UTI reduced the ability of PMA to trigger the uPA expression at the gene level and at the protein level. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 31 publications
4
58
0
Order By: Relevance
“…In addition, tumor necrosis factor (TNF)-is a cytotoxic cytokine that is produced in progressive amounts during the secretory phase. It has been reported that bikunin has an ability to inhibit expression of several cytokines including TNFby inflammatory cells or neoplastic cells (Kobayashi et al 2001). Here, we show that TNF-receptor (osteoprotegerin; see below) is constitutively overexpressed in bik / mouse ovary.…”
Section: Heat Shock Proteinmentioning
confidence: 69%
See 1 more Smart Citation
“…In addition, tumor necrosis factor (TNF)-is a cytotoxic cytokine that is produced in progressive amounts during the secretory phase. It has been reported that bikunin has an ability to inhibit expression of several cytokines including TNFby inflammatory cells or neoplastic cells (Kobayashi et al 2001). Here, we show that TNF-receptor (osteoprotegerin; see below) is constitutively overexpressed in bik / mouse ovary.…”
Section: Heat Shock Proteinmentioning
confidence: 69%
“…Interestingly, in the case of neoplastic cells, exposure of bikunin or bikunin gene transfection to cancer cells induces suppression of invasion and metastasis (Kobayashi et al 2002, Suzuki et al 2003a. Bikunin may modulate different intracellular signaling pathways including MAP (ERK) and phosphoinositide-3 (PI3) kinases (Akt), which lead to the down-regulation of the expression of urokinasetype plasminogen activator (uPA) (Kobayashi et al 2001(Kobayashi et al , 2003 and its receptor, uPAR (Nakamura et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, one can ask what the roles of PI3K/Akt and Erk pathways during early stage invasion of ovarian cancer cells are. Although those pathways have been previously identified as therapeutic targets, 9,10 in this report, activation of Met by fibronectin, unlike HGF/SF, did not activate Akt or Erk. We can then wonder whether activation of Akt/Erk pathways would be beneficial or not to the early stage attachement/invasion of those cells.…”
Section: Resultsmentioning
confidence: 68%
“…4C and D, TGF-h1 activation induced increased nuclear NF-nB The effect of thalidomide as well as neutralizing antibodies against urokinase-type plasminogen activator and urokinasetype plasminogen activator receptor on cell invasiveness. Our previous experiments showed that treatment with TGF-h1 produced a significant stimulation of the invasiveness of HRA cells in a dose-dependent manner, with a maximum stimulation at 10 ng/mL TGF-h1 (29). The uPA inhibitor amiloride (SigmaAldrich, Co.) was added to HRA cells in the upper chamber of the transwells at 100 Amol/L to study the effect of uPA inhibition on invasion.…”
Section: Resultsmentioning
confidence: 99%
“…Invasion assays were done essentially as described previously (29). The ability of cells to migrate across a Matrigel barrier (invasion) was determined by the modified Boyden chamber method.…”
Section: Methodsmentioning
confidence: 99%